MACROECONOMIC EFFECTS OF CONSUMER ETHNOCENTRISM IN BOSNIA AND HERZEGOVINA - Bešlagić, Amela; Bešlagić, Mirza (Poslovna ekonomija, 2024)
ABSTRACTThe subject of research in the paper is the social phenomenon of consumer ethnocentrism, which is characterized by an emotional state of attachment to everything that belongs to the country where the consumer lives. The aim of the paper was to analyze the macroeconomic effects of consumer ethnocentrism in Bosnia and Herzegovina. Losses for the national economy in terms of employment, production, taxes and contributions, as well as other social effects were analyzed with the assumption of substitution of imports by domestic production of products of the processing industry in Bosnia and Herzegovina, possible additional employment in manufacturing companies, and the effects of paid taxes and contributions for additional employment for pension and disability insurance, health insurance and unemployment insurance funds in Bosnia and Herzegovina in the period from 2009 to 2013. The amounts of losses per entities of the Federation of Bosnia and Herzegovina, Republic Srpska and Brčko District of Bosnia and Herzegovina were determined. The results of the research can serve as leverage for investments in domestic production, increasing employment, and creating commodity reserves that would be reflected in domestic products.
Keywords: national economy, consumer ethnocentrism, Bosnia and Herzegovina.